Clinical And Molecular-Genetic Features Of Congenital Aniridia - T.A. Vasilieva; Voskresenskaya A. A; V.V. Kadyshev; N.A. Pozdeeva; A.V. Marakhonov; R.A. Zinchenko (РМЖ "Клиническая офтальмология")
Vasilyeva T. A.1, Voskresenskaya A. A.2, Kadyshev V. V.1, Pozdeyeva N. A.2, Marakhonov A. V.1,3, Zinchenko R. A.1,4 1 Research Center for Medical Genetics, Moscow 2 Cheboksary branch of S. Fyodorov Eye Microsurgery Federal State Institution 3 Moscow Institute of Physics and Technology (State University), Dolgoprudny 4 Pirogov Russian National Research Medical University, Moscow Introduction: congenital aniridia (AN) is a Mendelian autosomal dominant disorder (population prevalence 1:57143). AN might occur as a part of WAGR syndrome (~13%). The main diagnostic signs of AN are absence of iris and fovea hypoplasia accompanied by nystagmus. Patients also show other eye structures as well as central nervous system anomalies. AN is caused by heterozygous mutations of the PAX6 gene or chromosome rearrangements of 11p13 region. There are no established correlation between the type of PAX6 mutation and the features of aniridia clinical picture. Aim: the paper is to analyze probable relations between AN clinical features and the type of PAX6 mutation. Patients and Methods: 98 patients with AN from 73 unrelated families with identified small PAX6 mutations (74 patients) and large chromosomal 11p13 deletions (24 patients) were analyzed. Patients were divided into the groups according to the type/location of mutation. Phenotypic traits were referred to the type/location of mutation. Contingency tables 2X2 were analyzed by the exact Fisher test. Results: AN clinical picture associated with loss of function mutations (nonsense, frame shift and splicing) has more severe clinical course. Missense mutations are associated with character phenotype of general sample, however, partial aniridia occurs significantly more often. Phenotypes of patients with chromosomal deletions (without deletions of the 3′ cis-regulatory region), do not differ from that of patients with intragenic mutations. A milder phenotype is observed in patients with deletions of the 3′ cis-regulatory region. Key words: congenital aniridia, PAX6 mutations, chromosome region 11p13 deletions, relationships between mutation type and clinical trait. For citation: Vasilyeva T.A., Voskresenskaya A.A., Kadyshev V.V. at all. Clinical and molecular-genetic features of congenital aniridia // RMJ “Clinical ophthalmology”. 2018;1:7–12.